Business productivity analysis of catfish (Clarias sp.) culture with additional probiotics and the effect on production cost efficiency - Buyung Purnomo Waluyo; Jefri Putri Nugraha; Ahmad Jibril (Sangia Research Media and Publishing, 2022)
This research aims to discover the effect of probiotics applications on the production revenue and cost efficiency of catfish culture. This research shows that the application of probiotics on the catfish feed can decrease the amount of FCR value, in which the value of FCR with probiotics is 0.96 within 1.11 without probiotics. This result shows that the best productivity of catfish was obtained by application of probiotics with productivity of 8.4 kg/m2, and R/C Ratio 1.35. Moreover productivity of catfish culture without probiotics application is 7.3 kg/m2 and R/C Ratio 1.18. Then the value of productivity based on unit costs produces a value of Rp. 11,176, - while for ponds without the addition of probiotics in the feed of Rp. 12,709, -Production values costs that must be incurred by farmers to produce 1 kg of catfish are lower in aquaculture that uses feed with probiotics so that profits will increase. These results suggested that the farmers can optimizing the use of probiotics to increase feed efficiency from the catfish rearing business without adding other inputs.